Covid-19 risk perception and anxiety of third-semester pregnant mothers in facing childbirth during the time of covid-19 pandemic in 2022 - Handayani, Sri; Putri, Sartika Dwi Yolanda (Universitas Aisyah Pringsewu, 2022)
Pregnant women have the most anxiety during the COVID-19 pandemic because they are vulnerable and at high risk. Excessive anxiety raises stress hormone levels in the body, which inhibits cervical dilatation and causes labor to take longer. Long delivery is one of the causes of Indonesia's high maternal mortality rate. The purpose of this study is to identify the factors that influence third-trimester pregnant women's worry about childbirth during the COVID-19 pandemic at the Kasihan I Community Health Center in 2022. The research design used was Cross-Sectional with an analytical survey method. Sampling was done by purposive sampling where the sample amounted to 74 respondents. Data were analyzed using univariate, bivariate, and multivariate logistic regression. The findings revealed a link between the perceived risk of COVID-19 and the anxiety of pregnant women in their third trimester about giving birth at the Kasihan I Community Health Center in 2022. The study's result was the varying perception of COVID-19 risk and the anxiety of pregnant women in their third trimester. Abstrak: Kecemasan yang dirasakan paling akut pada populasi rentan dan berisiko tinggi dimasa pandemi COVID-19 yaitu pada ibu hamil. Kecemasan yang berlebihan menyebabkan kadar hormon stres dalam tubuh meningkat dan menghambat dilatasi serviks, mengakibatkan persalinan lama. Persalinan lama merupakan salah satu penyebab tingginya angka kematian Ibu di Indonesia. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi kecemasan ibu hamil trimester III dalam menghadapi persalinan di masa pandemi COVID-19 di Puskesmas Kasihan I tahun 2022. Desain penelitian yang digunakan adalah Cross-Sectional dengan metode survey analitik. Pengambilan sampel dengan teknik purposive sampling, sampel berjumlah 74 responden. Data dianalisis secara univariat, bivariat dan multivariat menggunakan regresi logistik berganda. Hasil penelitian terdapat hubungan antara persepsi risiko COVID-19 dengan kecemasan ibu hamil Trimester III dalam menghadapi persalinan di Puskesmas Kasihan I Tahun 2022. Simpulan penelitian ini variabel persepsi risiko COVID-19 dengan kecemasan ibu hamil trimester III.